Isolation of virus-cell fusion inhibitory components from Eugenia caryophyllata - Kim, HJ; Lee, JS; Woo, ER; Kim, MK; Yang, BS; Yu, YG; Park, H; Lee, YS (GEORG THIEME VERLAG KG, 2001)
The fractionation of Eugenia caryophyllata (Myrtaceae) guided by the syncytia formation inhibition assay led to the isolation of four tannins (eugeniin, casuarictin. 1.3-di-O-galloyl-4,6-(S)-hexahydroxydiphenoyl-beta -D-glucopyranose and tellimagrandin I), and two chromones (biflorin and isobiflorin). Among the isolated compounds, tellimagrandin (4) showed a significantly high inhibitory activity on the syncytia formation with an IC50 value of 16.12 +/- 1.98 mug/ml.
Keywords: HYDROLYZABLE TANNINS; RETROVIRUSES; AIDS